2016
DOI: 10.1002/ajmg.a.37501
|View full text |Cite
|
Sign up to set email alerts
|

Novel missense mutations in a conserved loop between ERCC6 (CSB) helicase motifs V and VI: Insights into Cockayne syndrome

Abstract: Cockayne syndrome is caused by biallelic ERCC8 (CSA) or ERCC6 (CSB) mutations and is characterized by growth restriction, microcephaly, developmental delay, and premature pathological aging. Typically affected patients also have dermal photosensitivity. Although Cockayne syndrome is considered a DNA repair disorder, patients with UV-sensitive syndrome, with ERCC8 (CSA) or ERCC6 (CSB) mutations have indistinguishable DNA repair defects, but none of the extradermal features of Cockayne syndrome. We report novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…We further revealed that the basic patch of the H4 tail is dispensable for Rhp26 activities. This is in sharp contrast to ISWI and the Chd1 family, as the same basic patch is critical for ISWI-remodeling activities (19)(20)(21)(22)(23)47). Furthermore, unlike the case in ISWI that H4 tails can overcome the auto-inhibition by AutoN of ISWI, we found that the H4 tails cannot overcome the auto-inhibition imposed by the leucine-latch motif (Fig.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…We further revealed that the basic patch of the H4 tail is dispensable for Rhp26 activities. This is in sharp contrast to ISWI and the Chd1 family, as the same basic patch is critical for ISWI-remodeling activities (19)(20)(21)(22)(23)47). Furthermore, unlike the case in ISWI that H4 tails can overcome the auto-inhibition by AutoN of ISWI, we found that the H4 tails cannot overcome the auto-inhibition imposed by the leucine-latch motif (Fig.…”
Section: Discussioncontrasting
confidence: 61%
“…It binds the RNA polymerase II (Pol II) stalled complex at DNA damage sites and recruits downstream repair factors (such as CSA/ERCC8, TFIIH, XPA, and UVSSA) to repair DNA damage in the transcribed region (14)(15)(16)(17)(18). Mutations of the CSB/ERCC6 gene in humans lead to Cockayne syndrome, a rare neurological disorder that is characterized by premature aging, growth failure, and photosensitivity (10,14,19,20). CSB/ERCC6 proteins are highly conserved in most eukaryotic species (21), including Rad26 and Rhp26 in Saccharomyces cerevisiae and Schizosaccharomyces pombe, respectively (22)(23)(24).…”
mentioning
confidence: 99%
“…Clinical data was not available for 7 patients. Eighty-five patients from the Strasbourg database finally met the inclusion criteria to which 62 case-reports from the literature were added ( Brumback et al, 1978 ; Troelstra et al, 1992 ; Lehmann et al, 1993 ; Stefanini et al, 1996 ; Mallery et al, 1998 ; Colella et al, 1999 ; Meira et al, 2000 ; Falik-Zaccai et al, 2008 ; Hashimoto et al, 2008 ; Wilson et al, 2016b ; Kou et al, 2018 ; Sanchez-Roman et al, 2018 ). A total of 147 patients were included in the study, of whom 24 (16.3%) had 2U of PiggyBac, 18 (12.2%) had 1U1D of PiggyBac and 105 (71.4%) had 2D of PiggyBac ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…They often had learnt to read and write. For reported cases from the literature, the classification already established by the authors was taken into account except for two patients for whom classification was not mentioned in the original article ( Wilson et al, 2016b ). They were consequently classified by our expert committee based on available clinical data and pictures.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, W752 may provide a dual connection, on one side to the Rad26 ATP sensing elements, and on the other to the DNA fork. Strikingly, mutation of the functionally equivalent W936 residue in CSB has been reported to cause type I Cockayne syndrome 47 . Another key observation is that the number of persistent DNA contacts is much greater for the RecA2 domain as compared to RecA1.…”
Section: Resultsmentioning
confidence: 99%